A Rare Case of Metastatic Colon Cancer in a Patient With Squamous Cell Carcinoma of the Tongue. Issue 1 (13th January 2021) - Khan, Sikandar; Ur Rahman, Asad; Castillo, Michael; Riaz, Amir; Miret, Rafael; Bejarano, Pablo; Castro-Pavia, Fernando
ABSTRACT: Squamous cell carcinoma (SCC) of the colon, both primary and metastatic, are extremely rare malignancies. We present a case of a 60-year-old man with metastatic SCC of the tongue status after radiation and chemotherapy who presented with fatigue and melena. Colonoscopy revealed a 5 cm mass in the transverse colon. Pathology established the diagnosis of poorly differentiated SCC with p16 immunostaining, similar to biopsies from his initially diagnosed lingual cancer. To the best of our knowledge, there are no previously reported cases of primary SCC of the tongue metastasizing to the colon.